Correlates of Mathematics Anxiety among Business Studies Students: A Case of an Institution of Higher Learning in Malaysia - Kok, Heng Han; Vejaratnam, Navaratnam; Ithnan, Izwan Harith bin Md.; Zaid, Sumaiyah Mohd; Ismail, Norulhuda; Abbas, Mohd Saleh; Amin, Farah Azaliney Mohd (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper attempts to explore mathematics anxiety levels among students in a tertiary education institution. The data set was taken from a survey entitled “Exploring Mathematics Anxiety among Business Students in New Era University College (NEUC)”.The variables of study were measured using the Mathematics Anxiety Rating Scale (MARS) which developed by[1]. One-way ANOVA analysis was conducted to validate the impact of demographic factors drive their mathematics anxiety levels. The findings were based on descriptive and One-way Analysis of Variance. The results from this study show that poor performance in mathematics examinations in the past was associated with higher level of mathematics anxiety among the respondents. However, there was no significant difference in the level of mathematics anxiety across the academic levels and programs. This study would be significant for the educator to enhance their teaching style by offering educators the important information about mathematical anxiety during the learning process of students.